Antioxidant and Anti-Proliferative Properties of Hagenia abyssinica Roots and Their Potentially Active Components - Minxia Fan; Guilin Chen; Yongli Zhang; Lutfun Nahar; Satyajit Dey Sarker; Guangwan Hu; Mingquan Guo (MDPI AG, 2020)
Hagenia abyssinica (Bruce) J. F. Gmel. is a multipurpose dioecious tree that has been used to treat various ailments, for example, the flowers of H. abyssinica have been widely used as a tea to treat intestinal parasites by local residents and the roots of H. abyssinica could also be used for anticancer purposes. Antioxidant activity could be one of the most important pathways to suppress cancer and there is hardly any information available on the specific chemical components corresponding to the bioactivities of H. abyssinica to date. The present study intended to screen and evaluate the antioxidant and anti-proliferative properties of five different fractions from H. abyssinica along with their corresponding total flavonoid and phenolic contents and then further identify those compounds with the most potent antioxidant and anti-proliferative activities using high performance liquid chromatography (HPLC) coupled to mass spectrometry (MS) and nuclear magnetic resonance (NMR). The total flavonoid and phenolic content assays showed that the ethyl acetate (EA) fraction of H. abyssinica had higher flavonoid and phenolic levels than the other four fractions. Furthermore, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) superoxide radical scavenging abilities, total antioxidant capacity (TAC) assay with 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid (ABTS), and ferric-reducing antioxidant power (FRAP) were measured to evaluate the antioxidant activities of the five fractions and some pure compounds isolated from the EA fraction, which displayed higher antioxidant properties than that of the other fractions. Caffeic acid from the EA fraction showed even stronger DPPH scavenging ability (IC50 7.858 ± 0.31 µg/mL) than that of Vc (IC50 8.27 ± 0.11 µg/mL) as the positive control. The anti-proliferative properties of four fractions and the ethanol extract were evaluated by the 3-(4,5)-dimethylthiahiazo (-z-y1)-3,5-di-phenytetrazoliumromide (MTT) assay and the EA fraction exhibited higher anti-proliferative activities against three cancer cell lines than that of the other fractions. Additionally, the compounds with good antioxidant activity from the EA fraction of H. abyssinica were screened and identified using LC-MS and NMR and were also found to possess good anti-proliferative activity. In the MTT assay, the quercetin showed the strongest dose-dependent anti-proliferative activities to colon cancer cells (HT-29) and liver cancer cells (HepG2) among all of the compounds isolated. This study provided valuable information on the synergistic antioxidant and anti-proliferative properties of H. abyssinica.